Preparation process of TOPCon battery and TOPCon battery
By using picosecond laser grooving and femtosecond laser annealing technologies, damaged areas of TOPCon batteries can be precisely repaired, solving the damage problem caused by laser removal of silicon nitride layers and improving battery performance and reliability.
Patent Information
- Application Number
- CN202411037397.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-30
- Publication Date
- 2025-10-24
AI Technical Summary
Existing TOPCon batteries suffer damage to the battery surface during laser removal of the silicon nitride layer, resulting in the destruction of the passivation layer and affecting battery performance.
Picosecond laser grooving combined with femtosecond laser annealing technology is used to precisely repair damaged areas while avoiding impact on undamaged areas. Afterward, acid pickling and electroplating of the grid lines are performed.
It improves the battery's open-circuit voltage and fill factor, reduces recombination losses, enhances battery reliability and stability, and improves battery efficiency.
Smart Images

Figure CN120835630A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of solar cell preparation, in particular to a preparation process of a TOPCon cell and the TOPCon cell. BACKGROUND
[0002] TOPCon (Tunnel Oxide Passivated Contact) is a kind of high-efficiency solar cell technology, which is characterized by using a tunnel oxide layer and a polysilicon layer as a contact layer on the back surface of the cell, thereby realizing a lower surface recombination rate and a higher open-circuit voltage.
[0003] The TOPCon cell piece adopts an electroplating process to prepare a grid line electrode, and a laser is used to remove part of the silicon nitride layer (insulation) on the surface of the cell according to a design pattern, but the silicon nitride layer is removed, which causes damage to the surface of the cell piece. The existing rapid thermal annealing process (RTP) anneals the whole TOPCon cell piece at 300-600 DEG C to repair the laser damage, which has a negative impact on the non-damaged area during the repair process of the damaged position, destroys the H passivation effect in the passivation layer, and causes the Uoc and FF to decrease.
[0004] In view of this, the present application is proposed. SUMMARY
[0005] One of the purposes of the present application is to provide a preparation process of a TOPCon cell, which aims to solve at least one of the above technical problems in the prior art.
[0006] The second purpose of the present application is to provide a TOPCon cell.
[0007] In order to achieve the above purposes of the present application, the following technical solutions are adopted:
[0008] The first aspect of the present application provides a preparation process of a TOPCon cell, which is to sequentially perform laser slotting, laser annealing, acid pickling, electroplating of grid lines and light injection on a TOPCon blue film piece to obtain the TOPCon cell.
[0009] Further, the laser used for the laser slotting is a picosecond laser.
[0010] Preferably, the process of the laser slotting is to use a picosecond laser to slot the front surface and the back surface of the TOPCon blue film piece according to a grid line design pattern, and remove the silicon nitride layer on the TOPCon blue film piece.
[0011] Further, the laser annealing is performed on the damaged area of the laser slotting to repair it.
[0012] Preferably, the laser used in the laser annealing process is a femtosecond pulse laser.
[0013] Preferably, the frequency of the femtosecond pulsed laser is 30-100 MHz, preferably 50-80 MHz.
[0014] Preferably, the wavelength of the femtosecond pulsed laser is 200-800 nm, preferably 300-500 nm.
[0015] Preferably, the average power of the femtosecond pulsed laser is 5-20 W, preferably 8-10 W.
[0016] Further, the acid used in the pickling process is hydrofluoric acid.
[0017] Preferably, the mass percentage concentration of the hydrofluoric acid is 1-5%, preferably 1-3%.
[0018] Further, the preparation process of the TOPCon cell further comprises a cleaning process after the pickling and before the electroplating of the grid lines.
[0019] Preferably, deionized water is used for the cleaning process.
[0020] Further, the electroplating of the grid lines is performed in the groove formed by the laser grooving.
[0021] Preferably, the grid line structure is a nickel layer, a copper layer and a tin layer from the bottom layer to the surface layer.
[0022] Further, the thickness of the nickel layer is 0.5-2 μm, preferably 1-1.5 μm.
[0023] Preferably, the thickness of the copper layer is 5-15 μm, preferably 8-10 μm.
[0024] Preferably, the thickness of the tin layer is 0.5-2 μm, preferably 0.8-1.2 μm.
[0025] Further, in the light injection, the wavelength of the light is 350-900 nm.
[0026] Preferably, in the light injection, the intensity of the light is 10-30 suns, preferably 15-20 suns.
[0027] Further, in the light injection, the holding temperature is 100-300℃, preferably 150-200℃.
[0028] The second aspect of the present application provides a TOPCon cell prepared by the preparation process of the first aspect.
[0029] Compared with the prior art, the present application has at least the following beneficial effects:
[0030] The preparation process of the TOPCon cell provided by the application introduces a laser annealing process after laser grooving and before pickling, accurately repairs the damaged areas of the cell sheet, achieves the purpose of damage repair, does not affect the non-damaged areas, reduces the crystal defects that may be generated during the laser grooving process, thereby reducing the recombination loss of the cell and improving the efficiency of the cell; at the same time, the laser annealing improves the passivation effect of the tunnel oxide and the interface quality of the cell base and the metal contact, reduces the surface recombination rate, improves the contact resistance, thereby improving the open-circuit voltage (Uoc) and the fill factor (FF) of the cell. By setting the laser annealing process before pickling, the chemical damage of the cell sheet during pickling can be reduced, the surface of the cell sheet can be protected, and the reliability and stability of the cell can be improved.
[0031] The TOPCon cell provided by the application benefits from the innovation and advantages of the above preparation method, realizes significant performance improvement and substantial efficiency improvement, and provides new power and direction for the development of the photovoltaic industry. BRIEF DESCRIPTION OF DRAWINGS
[0032] In order to more clearly illustrate the specific embodiments of the application or the technical solutions in the prior art, the drawings needed in the description of the specific embodiments or the prior art will be briefly introduced. Obviously, the drawings in the following description are some embodiments of the application, and other drawings can also be obtained by those skilled in the art without creative labor.
[0033] Figure 1 It is a structural schematic diagram of the TOPCon cell.
[0034] Figure legend: 100-N type silicon substrate; 200-front surface of N type silicon substrate; 300-back surface of N type silicon substrate; 210-boron diffusion layer; 220-aluminum oxide layer; 230-first silicon nitride layer; 240-first nickel layer; 250-first copper layer; 260-first tin layer; 310-tunnel oxide layer; 320-polysilicon layer; 330-second silicon nitride layer; 340-second nickel layer; 350-second copper layer; 360-second tin layer. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical scheme and advantages of the application more clear, the technical scheme in the embodiments of the application will be described clearly and completely below in combination with the embodiments of the application. Obviously, the described embodiments are only some of the embodiments of the application, not all the embodiments.
[0036] Hereinafter, the terms "include", "have", and their conjugations, which can be used in various embodiments of the present application, are merely intended to denote a specific feature, number, step, operation, component, part, or combination thereof, and are not intended to exclude the existence of or a possibility of addition of one or more other features, numbers, steps, operations, components, parts or combinations thereof.
[0037] As shown in FIG. 1, the structure of the TOPCon cell includes an N-type silicon substrate 100, a front surface 200 of the N-type silicon substrate, and a back surface 300 of the N-type silicon substrate. Figure 1 The front surface 200 of the N-type silicon substrate 100 includes a boron diffusion layer 210, an aluminum oxide layer 220, and a first silicon nitride layer 230, which are sequentially stacked on the N-type silicon substrate 100. The back surface 300 includes a tunneling oxide layer 310, a polysilicon layer 320, and a second silicon nitride layer 330, which are sequentially stacked on the N-type silicon substrate 100.
[0038] The front surface 200 of the N-type silicon substrate and the back surface 300 of the N-type silicon substrate are each independently provided with a wire slot, and a gate line is arranged in the wire slot. The gate line of the front surface 200 of the N-type silicon substrate includes a first nickel layer 240, and the first nickel layer 240 is in contact with the bottom of the wire slot of the front surface 200 of the N-type silicon substrate, and the first nickel layer 240 is in contact with the N-type silicon substrate 100. The first nickel layer 240 is covered with a first copper layer 250 and a first tin layer 260 from bottom to top.
[0039] The gate line of the back surface 300 of the N-type silicon substrate includes a second nickel layer 340, and the second nickel layer 340 is in contact with the bottom of the wire slot of the back surface 300 of the N-type silicon substrate, and the second nickel layer 340 is in contact with the polysilicon layer 320. The second nickel layer 340 is covered with a second copper layer 350 and a second tin layer 360 from bottom to top.
[0040] The gate line of the back surface 300 of the N-type silicon substrate includes a second nickel layer 340, and the second nickel layer 340 is in contact with the bottom of the wire slot of the back surface 300 of the N-type silicon substrate, and the second nickel layer 340 is in contact with the polysilicon layer 320. The second nickel layer 340 is covered with a second copper layer 350 and a second tin layer 360 from bottom to top.
[0041] The first aspect of the present application provides a preparation process of a TOPCon cell, which comprises sequentially performing laser slotting, laser annealing, acid washing, electroplating of a gate line, and light injection on a TOPCon blue film piece to obtain the TOPCon cell.
[0042] The TOPCon battery preparation process provided by the present invention introduces a laser annealing process after laser grooving and before pickling to precisely repair damaged areas of the battery cell. This not only achieves the purpose of damage repair, but also does not affect non-damaged areas, reducing crystal defects that may be generated during the laser grooving process, thereby reducing battery recombination losses and improving battery efficiency. At the same time, laser annealing improves the passivation effect of the tunnel oxide and the interface quality between the battery substrate and the metal contact, reducing the surface recombination rate and increasing the contact resistance, thereby improving the battery's open circuit voltage (Uoc) and fill factor (FF). Placing the laser annealing process before pickling can also reduce the chemical damage to the battery cell during the pickling process, protect the battery cell surface, and improve the reliability and stability of the battery.
[0043] Furthermore, the laser used for the laser grooving is a picosecond laser.
[0044] Picosecond laser refers to a laser with a pulse width of 10 -12 Picosecond lasers have higher precision and lower damage, and can perform precise cutting and grooving on micron-level devices, improving the performance and reliability of the prepared TOPCon cells.
[0045] Preferably, the laser grooving process is to use a picosecond laser to perform grooving on the front and back sides of the TOPCon blue diaphragm according to the grid line design pattern, thereby removing the silicon nitride layer on the TOPCon blue diaphragm.
[0046] By using a picosecond laser to precisely groove the front and back of the TOPCon blue diaphragm according to the grid line design pattern, not only is the efficient removal of the silicon nitride layer achieved, but the high accuracy of the grooving process and the gentle handling of the blue diaphragm are also ensured. The ultra-short pulse characteristics of the picosecond laser greatly reduce the heat-affected zone, effectively avoiding thermal damage or thermal stress accumulation to the silicon wafer material, thereby maintaining the integrity and electrical properties of the silicon wafer. In addition, picosecond laser grooving can achieve finer line width control and lower side roughness, which is of great significance for improving the photoelectric conversion efficiency and long-term stability of solar cells. Through this optimized grooving process, the performance of TOPCon solar cells has been significantly improved, showing higher energy output and longer service life.
[0047] Furthermore, the laser annealing is performed on the damaged area of the laser grooving to repair it.
[0048] Preferably, during the laser annealing process, the laser is a femtosecond pulse laser.
[0049] Femtosecond pulse laser is similar to picosecond laser, which means the pulse width is 10 -15The femtosecond pulse laser has an extremely high peak power, which can deliver energy to the material in a very short time, and is suitable for precise machining at micron or even nanometer level.
[0050] Preferably, the frequency of the femtosecond pulse laser is 30MHz-100MHz, preferably 50MHz-80MHz.
[0051] Typically but not limitedly, the frequency of the femtosecond pulse laser may, for example, be 30MHz, 40MHz, 50MHz, 60MHz, 70MHz, 80MHz, 90MHz or 100MHz, or any value within the range of 30MHz-100MHz. Within the preferred range, the frequency of the femtosecond pulse laser may, for example, be 50MHz, 55MHz, 60MHz, 65MHz, 70MHz, 75MHz, 80MHz, or any value within the range of 50MHz-80MHz.
[0052] Preferably, the wavelength of the femtosecond pulse laser is 200nm-800nm, preferably 300nm-500nm.
[0053] Typically but not limitedly, the wavelength of the femtosecond pulse laser may, for example, be 200nm, 220nm, 240nm, 260nm, 280nm, 300nm, 320nm, 340nm, 360nm, 380nm, 400nm, 420nm, 440nm, 460nm, 480nm, 500nm, 520nm, 540nm, 560nm, 580nm, 600nm, 620nm, 640nm, 660nm, 680nm, 700nm, 720nm, 740nm, 760nm, 780nm or 800nm, or any value within the range of 200nm-800nm. Preferably, the wavelength of the femtosecond pulse laser may, for example, be 300nm, 310nm, 320nm, 330nm, 340nm, 350nm, 360nm, 370nm, 380nm, 390nm, 400nm, 410nm, 420nm, 430nm, 440nm, 450nm, 460nm, 470nm, 480nm, 490nm or 500nm, or any value within the range of 300nm-500nm.
[0054] Preferably, the average power of the femtosecond pulse laser is 5W-20W, preferably 8W-10W.
[0055] Typically but not limitedly, the average power of the femtosecond pulsed laser may be, for example, 5 W, 6 W, 7 W, 8 W, 9 W, 10 W, 11 W, 12 W, 13 W, 14 W, 15 W, 16 W, 17 W, 18 W, 19 W or 20 W, or any value within the range of 5 W to 20 W. In a preferred range, it may be, for example, 8 W, 8.5 W, 9 W, 9.5 W, 10 W, or any value within the range of 8 W to 10 W.
[0056] With the frequency, wavelength and average power of the femtosecond pulsed laser within the above ranges, the TOPCon blue film piece can be heated to a high temperature in a very short time, and then rapidly cooled to change the performance of the TOPCon blue film piece, effectively repairing defects on the surface of the TOPCon blue film piece, such as grain boundaries or dislocations, etc.; at the same time, the heat-affected zone of the TOPCon blue film piece is reduced, and the microstructure and performance of the TOPCon blue film piece are maintained.
[0057] The technical features of using a femtosecond pulsed laser for laser annealing provide an efficient and precise method for repairing damaged areas during laser grooving. In this process, the ultra-short pulse width and high repetition frequency of the femtosecond laser enable energy to be absorbed by the local area at a very fast speed, thereby accurately heat-treating the damaged area without damaging the surrounding material. By setting the laser frequency between 30 MHz and 100 MHz, preferably between 50 MHz and 80 MHz, the continuity and uniformity of the treatment process are ensured. At the same time, the laser wavelength is selected within the range of 200 nm to 800 nm, preferably between 300 nm and 500 nm, which can effectively interact with the material and promote the repair of the damaged area. In addition, by adjusting the average power of the femtosecond pulsed laser to be between 5 W and 20 W, preferably between 8 W and 10 W, the annealing effect can be optimized to ensure that the lattice structure and electrical properties of the material are effectively restored. The application of this laser annealing technology significantly improves the quality and efficiency of material repair, and has important value for improving the performance and reliability of devices.
[0058] Further, the acid used in the pickling process is hydrofluoric acid.
[0059] Preferably, the mass percentage concentration of the hydrofluoric acid is 1% to 5%, preferably 1% to 3%.
[0060] Typically but not limitedly, the mass percentage concentration of the hydrofluoric acid may be, for example, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4% or 5%, or any value within the range of 1% to 5%. In particular, the preferred mass percentage concentration of the hydrofluoric acid may be, for example, 1%, 1.25%, 1.5%, 1.75%, 2%, 2.25%, 2.5%, 2.75% or 3%, or any value within the range of 1% to 3%.
[0061] The technical feature of using hydrofluoric acid for acid washing provides an effective method for material surface treatment. Due to its unique chemical properties, hydrofluoric acid can react with materials such as silicon to remove surface oxide layers or other impurities, thereby achieving the purpose of cleaning and activating the surface. Under preferred conditions, the mass percentage concentration of hydrofluoric acid is controlled within the range of 1% to 5%, and more specifically between 1% and 3%. Such a concentration range not only ensures the significance of the acid washing effect, but also reduces the risk of corrosion that may be caused by excessively high acid concentration.
[0062] Further, the preparation process of the TOPCon cell also includes a cleaning process after the acid washing and before the electroplating of the grid lines;
[0063] Preferably, deionized water is used for the cleaning process to remove residual acid from the acid washing process.
[0064] The cleaning process after the acid washing step and before the electroplating of the grid lines is a key technical link to ensure that the surface of the silicon wafer is in the best state for the next process. This cleaning process effectively removes acid and other impurities that may remain on the surface of the silicon wafer after acid washing, preventing these residues from having a negative impact on the subsequent electroplating of the grid lines. Preferably, deionized water is used for cleaning, not only because its high purity ensures that no new impurities are introduced, but also because its good cleaning ability effectively removes residues from the surface of the silicon wafer. In addition, the mild nature of deionized water avoids secondary damage or contamination to the surface of the silicon wafer, providing a guarantee for the uniformity and adhesion of the electroplated grid lines.
[0065] Further, the electroplating of the grid lines is performed in the grooves formed by laser grooving.
[0066] Preferably, the grid line structure is a nickel layer, a copper layer, and a tin layer from the bottom layer to the surface layer.
[0067] The grid lines improve the conductivity and durability of the electrodes. The nickel layer as the bottom layer provides good adhesion and corrosion resistance, ensuring the firm combination of the grid lines with the silicon wafer; the copper layer as the intermediate layer has excellent conductivity, effectively reducing the resistivity and improving the power transmission efficiency of the battery; the tin layer as the top layer not only further enhances the corrosion resistance of the grid lines, but also helps to improve the solderability of the grid lines.
[0068] Further, the thickness of the nickel layer is 0.5 μm to 2 μm, preferably 1 μm to 1.5 μm.
[0069] The thickness of the nickel layer within the range of 0.5 μm to 2 μm can form good adhesion with the bottom layer of the TOPCon blue film wafer, improve the stability of the electroplated structure, reduce the peeling phenomenon during the electroplating process, and improve the reliability of the nickel layer structure.
[0070] Typically but not exclusively, the thickness of the nickel layer can be, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm or 2.0 μm, or any value within the range of 0.5 μm to 2 μm. Within a preferred range, the thickness of the nickel layer can be, for example, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm or 1.5 μm, or any value within the range of 1 μm to 1.5 μm.
[0071] Preferably, the thickness of the copper layer is 5 μm to 15 μm, preferably 8 μm to 10 μm.
[0072] The thickness of the copper layer within the range of 5 μm to 15 μm reduces the electrical resistivity, increases the transmission speed and efficiency of the charge carriers, and reduces the heat accumulation during the transmission of the charge carriers, thereby reducing the adverse effects of the thermal effects on the transmission of the charge carriers.
[0073] Typically but not exclusively, the thickness of the copper layer can be, for example, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, or any value within the range of 5 μm to 15 μm. Within a preferred range, the thickness of the copper layer can be, for example, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or any value within the range of 8 μm to 10 μm.
[0074] Preferably, the thickness of the tin layer is 0.5 μm to 2 μm, preferably 0.8 μm to 1.2 μm.
[0075] The thickness of the tin layer within the range of 0.5 μm to 2 μm protects the copper layer from oxidation or corrosion, increases the electrochemical stability of the electrode, reduces the contact resistance between the electrode and the external circuit, and increases the transmission efficiency of the charge carriers. At the same time, the tin layer has better compatibility with the welding material, reduces the contact resistance during the welding process, and improves the welding quality.
[0076] Typically but not exclusively, the thickness of the tin layer can be, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm or 2.0 μm, or any value within the range of 0.5 μm to 2 μm. Within a preferred range, the thickness of the tin layer can be, for example, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm or 1.2 μm, or any value within the range of 0.8 μm to 1.2 μm.
[0077] Further, in the light injection, the wavelength of the light is 350-900 nm.
[0078] Typically but not exclusively, in the light injection process, the wavelength of the light can be, for example, 350 nm, 400 nm, 450 nm, 500 nm, 550 nm, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, or 900 nm, or any value within the range of 350 nm to 900 nm.
[0079] Preferably, in the light injection, the intensity of the light is 10-30 sun, preferably 15-20 sun.
[0080] Typically but not exclusively, in the light injection process, the intensity of the light can be, for example, 10 sun, 12 sun, 14 sun, 16 sun, 18 sun, 20 sun, 22 sun, 24 sun, 26 sun, or 30 sun, or any value within the range of 10 sun to 30 sun. In particular, the preferred intensity range of the light can be 15 sun, 16 sun, 17 sun, 18 sun, 19 sun, or 20 sun, or any value within the range of 15 sun to 20 sun.
[0081] The wide wavelength range of light injection covers most of the spectrum from ultraviolet to visible light, ensuring that the solar cell can capture a wider spectrum of sunlight and convert it into electrical energy. Such light intensity not only effectively simulates the irradiation conditions of real sunlight, but also, by increasing the light intensity, can more deeply excite the photoelectric effect in the solar cell, thereby increasing the photocurrent and voltage of the cell and further improving the output power of the cell.
[0082] Further, in the light injection, the holding temperature is 100-300°C, preferably 150-200°C.
[0083] This temperature range ensures that the material can achieve the best thermal excitation state during the light injection process, thereby promoting the reorganization of the electronic structure and the repair of defects within the material. This temperature control not only helps to improve the efficiency of light injection, but also optimizes the photoelectric conversion performance of the cell. Within the preferred temperature range of 150°C to 200°C, the thermal excitation effect of the material is more pronounced, which helps to further improve the open-circuit voltage and fill factor of the solar cell, thereby achieving higher energy conversion efficiency and better long-term stability.
[0084] Typically but not exclusively, the holding temperature in the light injection treatment can be, for example, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, 160℃, 170℃, 180℃, 190℃, 200℃, 210℃, 220℃, 230℃, 240℃, 250℃, 260℃, 270℃, 280℃, 290℃ or 300℃, or any value within the range of 100℃ to 300℃. In particular, the preferred holding temperature range can be 150℃, 152℃, 154℃, 156℃, 158℃, 160℃, 162℃, 164℃, 166℃, 168℃, 170℃, 172℃, 174℃, 176℃, 178℃, 180℃, 182℃, 184℃, 186℃, 188℃, 190℃, 192℃, 194℃, 196℃, 198℃ or 200℃, or any value within the range of 150℃ to 200℃.
[0085] The second aspect of the present application provides a TOPCon cell prepared by the preparation process of the first aspect.
[0086] The TOPCon cell provided by the present application has the advantages of the above preparation method, and has significantly improved performance and greatly improved efficiency, providing new power and direction for the development of the photovoltaic industry.
[0087] The present application will be further described below through specific examples and comparative examples, but it should be understood that these examples are only for more detailed description and should not be understood as limiting the present application in any form. The raw materials used in the examples and comparative examples of the present application are prepared according to the conventional conditions or the conditions recommended by the manufacturer if no specific conditions are specified. The reagents or instruments used are conventional products that can be purchased on the market if no manufacturer is specified.
[0088] Example 1
[0089] The present embodiment provides a TOPCon cell, and the specific preparation steps are as follows:
[0090] 1. Select the TOPCon blue film piece semi-finished product before electroplating. The semi-finished product is completed according to the normal TOPCon production process.
[0091] 2. Use a picosecond laser to perform laser silicon nitride layer removal operation on the front and back surfaces of the cell piece according to the designed grid line pattern. This step is to form the required grooves on the cell piece.
[0092] 3. Select a femtosecond pulse laser with a wavelength of 500 nm, an average power of 12 W and a pulse frequency of 60 MHz to anneal and repair the front slot damage area formed in step 2.
[0093] 4. The blue film piece after laser annealing is immersed in 5% dilute hydrofluoric acid for cleaning to remove the silicon dioxide that may be generated in the annealing process. After cleaning, deionized water is used for further cleaning to remove the residual hydrofluoric acid.
[0094] 5. An electroplating process is used to plate different thicknesses of metal layers on the laser slotted positions in sequence. First, a 1 μm nickel layer is plated, followed by a 10 μm copper layer, and finally a 1 μm tin layer is plated to complete the electroplating of the double-sided grid lines of the cell piece.
[0095] 6. The cell piece after the grid line fabrication is subjected to light injection treatment. In the light injection process, the light injection temperature is 200°C, and the light intensity is 17 suns.
[0096] 7. The cell piece after the light injection treatment is subjected to IV testing, and is graded according to different powers based on the test results to ensure that the performance of the cell piece meets the requirements, and a TOPCon cell is obtained.
[0097] Example 2
[0098] This example provides a TOPCon cell, and the specific preparation steps are as follows:
[0099] 1. This step is the same as that in Example 1.
[0100] 2. This step is the same as that in Example 1.
[0101] 3. A femtosecond pulsed laser with a wavelength of 400 nm, an average power of 14 W, and a pulse frequency of 90 MHz is selected to anneal and repair the front slotted damage area formed in step 2.
[0102] 4. This step is the same as that in Example 1.
[0103] 5. This step is the same as that in Example 1.
[0104] 6. This step is the same as that in Example 1.
[0105] 7. This step is the same as that in Example 1.
[0106] Example 3
[0107] This example provides a TOPCon cell, and the specific preparation steps are as follows:
[0108] 1. This step is the same as that in Example 1.
[0109] 2. This step is the same as that in Example 1.
[0110] 3. A femtosecond pulsed laser with a wavelength of 600 nm, an average power of 8 W, and a pulse frequency of 30 MHz is selected to anneal and repair the front slotted damage area formed in step 2.
[0111] 4. The same as the step of Example 1.
[0112] 5. The same as the step of Example 1.
[0113] 6. The same as the step of Example 1.
[0114] 7. The same as the step of Example 1.
[0115] Example 4
[0116] This example provides a TOPCon cell, and the specific preparation steps are as follows:
[0117] 1. The same as the step of Example 1.
[0118] 2. The same as the step of Example 1.
[0119] 3. A femtosecond pulse laser with a wavelength of 200 nm, an average power of 5 W, and a pulse frequency of 100 MHz is selected to anneal and repair the front slot damage area formed in step 2.
[0120] 4. The same as the step of Example 1.
[0121] 5. The same as the step of Example 1.
[0122] 6. The same as the step of Example 1.
[0123] 7. The same as the step of Example 1.
[0124] Example 5
[0125] This example provides a TOPCon cell, and the specific preparation steps are as follows:
[0126] 1. The same as the step of Example 1.
[0127] 2. The same as the step of Example 1.
[0128] 3. A femtosecond pulse laser with a wavelength of 800 nm, an average power of 20 W, and a pulse frequency of 30 MHz is selected to anneal and repair the front slot damage area formed in step 2.
[0129] 4. The same as the step of Example 1.
[0130] 5. The same as the step of Example 1.
[0131] 6. The same as the step of Example 1.
[0132] 7. The same as the step of Example 1.
[0133] Example 6
[0134] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the frequency of the femtosecond pulse laser is 20 MHz, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0135] Embodiment 7
[0136] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the frequency of the femtosecond pulse laser is 120 MHz, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0137] Embodiment 8
[0138] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the wavelength of the femtosecond pulse laser is 100 nm, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0139] Embodiment 9
[0140] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the wavelength of the femtosecond pulse laser is 1000 nm, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0141] Embodiment 10
[0142] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the average power of the femtosecond pulse laser is 3 W, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0143] Embodiment 11
[0144] The embodiment provides a TOPCon cell, which is different from the embodiment 1 in that in step 3, the average power of the femtosecond pulse laser is 30 W, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0145] Comparative Example 1
[0146] The comparative example provides a TOPCon cell, which is different from the embodiment 1 in that step 3 is omitted, and after forming the groove required for the grid line in step 2, the process directly enters the hydrofluoric acid cleaning process in step 4, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0147] Comparative Example 2
[0148] The comparative example provides a TOPCon cell, which is different from the embodiment 1 in that the order of step 3 and step 4 is exchanged, and step 4 is performed first and then step 3 is performed, and the remaining steps and parameters are the same as those of the embodiment 1, which are not described herein again.
[0149] Test Example 1
[0150] The TOPCon cells obtained by the examples and comparative examples were made into the same specification, and the electrical performance detection was carried out, including photoelectric conversion efficiency and open-circuit voltage.
[0151] Specifically, IV test was used, and the data obtained under the condition of temperature of 25℃ and AM of 1.5G were shown in Table 2.
[0152] In Table 2, Eta(%) refers to the efficiency of the solar cell, which refers to the efficiency of the solar cell in converting the received solar radiation energy into electrical energy, and is usually expressed in percentage. Uoc(V) is the open-circuit voltage. It refers to the voltage when there is no current flowing through the solar cell (i.e. when the circuit is disconnected). The open-circuit voltage is the voltage value that the battery can provide without load, and the unit is V. Isc(A) refers to the short-circuit current, which refers to the current flowing through the battery when the two ends of the solar cell are directly short-circuited. The short-circuit current is the current value that the battery can provide without external load, and the unit is A. FF(%) is the fill factor, which refers to the product of the ratio of the current and voltage under actual working state of the solar cell to the current and voltage under ideal condition (i.e. the current and voltage at the maximum power point), and is usually expressed in percentage.
[0153] Table 1
[0154]
[0155]
[0156] As can be seen from Table 1, the increase of step 3 improves the efficiency of the TOPCon plating cell, and the open voltage and FF are improved more obviously.
[0157] Finally, it should be noted that the above-described examples are only specific embodiments of the present application, which are used to illustrate the technical solutions of the present application, but not to limit it. The protection scope of the present application is not limited to this. Although the present application has been described in detail with reference to the foregoing examples, those skilled in the art should understand that any person skilled in the art can modify or easily think of changes to the technical solutions recorded in the foregoing examples within the technical range disclosed by the present application, or make equivalent replacement to some technical features thereof. Such modifications, changes or replacements do not make the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application, and should be covered within the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.
Claims
1. A process for preparing a TOPCon cell, characterized in that, The TOPCon blue film piece is sequentially subjected to laser slotting, laser annealing, acid pickling, grid line electroplating and light injection to obtain the TOPCon cell.
2. The manufacturing process according to claim 1, characterized in that, The laser used in the laser slotting is a picosecond laser; Preferably, the process of laser slotting is to use a picosecond laser to slot the front and back surfaces of the TOPCon blue film piece according to a grid line design pattern, and remove the silicon nitride layer on the TOPCon blue film piece.
3. The manufacturing process of claim 1, wherein, The laser annealing is performed on the damaged area of the laser slotting to repair it; Preferably, the laser used in the laser annealing is a femtosecond pulse laser; Preferably, the frequency of the femtosecond pulse laser is 30-100 MHz, preferably 50-80 MHz. Preferably, the wavelength of the femtosecond pulse laser is 200-800 nm, preferably 300-500 nm. Preferably, the average power of the femtosecond pulse laser is 5-20 W, preferably 8-10 W.
4. The process according to any one of claims 1 to 3, characterized in that, The acid used in the acid pickling process is hydrofluoric acid; Preferably, the mass percentage concentration of the hydrofluoric acid is 1-5%, preferably 1-3%.
5. The process according to any one of claims 1 to 3, characterized in that, The process further comprises a cleaning process after the acid pickling and before the grid line electroplating; Preferably, deionized water is used in the cleaning process.
6. The process according to any one of claims 1 to 3, characterized in that, The grid line electroplating is performed in the slot formed by the laser slotting; Preferably, the grid line structure is a nickel layer, a copper layer and a tin layer from the bottom layer to the surface layer.
7. The manufacturing process of claim 6, wherein, The thickness of the nickel layer is 0.5-2 μm, preferably 1-1.5 μm; Preferably, the thickness of the copper layer is 5-15 μm, preferably 8-10 μm; Preferably, the thickness of the tin layer is 0.5-2 μm, preferably 0.8-1.2 μm.
8. The process according to any one of claims 1 to 3, characterized in that, In the light injection, the wavelength of the light is 350-900 nm; Preferably, in the light injection, the intensity of the light is 10-30 sun, preferably 15-20 sun.
9. The process according to any one of claims 1 to 3, characterized in that, In the light injection, the holding temperature is 100-300℃, preferably 150-200℃.
10. A TOPCon cell, characterized in that, The preparation process is prepared by any one of claims 1-9. The preparation process is prepared by any one of claims 1-9.